Grizzly bear - Penny, Malcolm (Burbank : Warner Home Video Inc., 1993)
Alaska is one of the last home ranges where people still confront this legendary creature on its own terms. Here the incredible accounts and dramatic lessons of the those who enter bear country
Title from data sheet
Keywords: Grizzly bear